Processing and modeling of conductive thermoplastic/carbon nanotube films for strain sensing - Pham, Giang T.; Park, Young-Bin; Liang, Zhiyong; Zhang, Chuck; Wang, Ben (Composites. Part B, Engineering, 2008)
This paper reports the development of conductive, carbon nanotube (CNT)-filled, polymer composite films that can be used as strain sensors with tailored sensitivity. The films were fabricated via either melt processing or solution casting of poly(methyl methacrylate) (PMMA) matrices containing low concentrations of multi-walled carbon nanotubes (MWNTs). The electrical resistivities of the films were measured in situ using laboratory-designed fixtures and data acquisition system. The measured resistivities were correlated with the applied strains to evaluate the sensitivity of the nanocomposite film sensor. The study suggests that conductive network formation, thus strain sensitivity of the conductive films, can be tailored by controlling nanotube loading, degree of nanotube dispersion, and film fabrication process. The developed sensors exhibited a broad range of sensitivity, the upper limit showing nearly an order of magnitude increase compared to conventional, resistance-type strain gages. A semi-empirical model that shows the relationship between CNT volume fraction and sensitivity is proposed.